Martha Bayless, Parody in the Middle Ages. The latin tradition - Alejandro Higashi (Medievalia, 2016)
Martha Bayless, Parody in the Middle Ages. The latin tradition, Ann Arbor: University of Michigan Press, 1996 (Recentiores: Later latin texts & contexts), xii + 425pp.